Behavioural study of Nymphs of Periplaneta americana in a Light-Dark Box Subjected to Different Environmental conditions - Nending Muni; Trinity Sherpaa; Dilukshi Shashikaran (Dera Natung Government College Research Journal)
Nymphs of Periplaneta americana were used as an insect model to test behavioral changes in light-dark box experimental setup in relation to circadian rhythm disruption. The present study is focused mainly on light and dark preferences based on the three parameters of responses by a nymph of P. Americana in different environmental conditions by using light-dark box. The nymphs under constant light (LL) and constant darkness (DD) exposure were found to exhibit higher behavioral response in light-dark box test (Mean±SEM) when compared to 12 hours light-12 hours darkness LD condition.